Some Reflections on the Execution of Concession Contracts: Interpretation, Amendments and Settlements of Disputes - Menchola Arana, Muriel (2015)
This document aims to expose some reflections on the dynamics of the concession contracts during the execution period, incomplete contracts that by its nature and by its long duration require an intensive work by the parties intended to interpret, define and / or clarify the agreed terms, as well as negotiation and signing of the new agreements to amend the text and, finally, the settlement of disputes. In addition to the characteristics of concession contracts described above, we also should take note of its unique and mixed nature, which is a consequence of the fact that this kind of contracts are rule by the public laws whose purpose is to safeguard the public interest through the implementation of infrastructure projects and public services - and also by the private laws- in which takes precedence the autonomy of the parties, consent and good faith. This article reviews how it is that these characteristics of the Concession Contract have been reflected in our legal system and, if necessary, make some kind of conformity and / or correction.